Comparison of catalytic activity between Au(110) and Au(111) for the electro-oxidation of methanol and formic acid: Experiment and density functional theory calculation. (1st December 2017) - Shen, Kechang; Jia, Cungui; Cao, Boxuan; Xu, Hui; Wang, Jin; Zhang, Laichang; Kim, Kibuem; Wang, Weimin
Graphical abstract: Abstract: The catalytic activities of Au(110) and Au(111) electrodes for the electro-oxidation of methanol (CH3 OH) and formic acid (HCOOH) are compared by the cyclic voltammetry (CV) and density functional theory (DFT) calculations. The experimental results show that the Au(111) electrode exhibits a higher catalytic activity than Au(110) electrode for two tested electrolytes. The difference of oxide film formed on two electrode surfaces is indicated by the charge transfer rate constant ( k s ). The DFT calculated hybridization degree of Au 5d and O 2p electrons and amount of adsorption site of OH − anion give support to a higher catalytic activity of Au(111) electrode. The DFT calculated adsorption energy of OH − anion ( ε ads ) explains the different oxide amounts on two electrodes. These results suggest that the oxide formed on Au surface in CH3 OH solution plays a different role in the electro-oxidation from that in HCOOH solution.